Characterization of 3d (65:35) poly(lactic-co-glycolic acid) incorporated with fibrin and atelocollagen scaffolds using scanning electron microscopy, porosity and swelling tests - Mohamed Amin, Muhammad Azri Ifwat; Md Ali @ Tahir, Aisyah Hanani; Azhim, Azran; Mohamed Sideek, Mohamed Arshad; Sha'ban, Munirah (TERMIS, 2018)
Scaffolds play a role as a temporary framework and an extracellular matrix substitute for cultured cells. They provide cells growth substrate and promote mechanical integrity for the newly formed tissues. Previous studies indicated that there were many limitations when natural or synthetic scaffolds material is applied individually. To overcome this, hybrid scaffolds have been introduced for tissue regeneration by studying cellular interactions with relevant scaffolds. However, this present study only focused on fabrication and characterization of three-dimensional (3D) poly(lactic-co-glycolic acid) (PLGA) incorporated with fibrin (PF), atelocollagen (PA) and both fibrin and atelocollagen (PFA) scaffolds materials. The PLGA (mole ratio 65:35) scaffolds were fabricated using solvent casting and salt leaching method. The PA and PFA were crosslinked using 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) and 20mM N-hyroxysuccinimide (NHS). The interaction of incorporated scaffolds materials with PLGA were demonstrated through the notable peaks of amide bonds, as shown by the attenuated total reflectance Fourier transform infrared (ATR-FTIR). Other evaluations included the observation using scanning electron microscopy (SEM), the interconnection of pore structures (porosity), and water uptake capacity (swelling) of the scaffolds. The SEM showed the interconnection between pores in the scaffolds. This is supported by the increased of total porosity in PLGA after the incorporation of fibrin, atelocollagen and both fibrin and atelocollagen. Despite its hydrophobicity, PLGA alone group exhibited the highest percentage of water uptake compared to other hybrid scaffolds namely PF, PA and PFA. Based on the preliminary results, the PLGA based scaffolds may have potential to be used in tissue engineering application.